EFFECT OF TRACE ELEMENT FERTILIZERS ON CHANGES IN THE THICKNESS AND SURFACE OF COTTON LEAF (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In this article, when fed through cotton leaves with NPK microelements made from local raw materials, the thickness of the cotton seedling and the surface of the leaf surface increased as a result of the suspensions applied through the leaf, the process of photosynthesis is accelerated, the metabolism is improved, and as a result, the plant Information about the optimal development and increase in cotton yield is provided.